RARE-33. LEPTOMENINGEAL DISEASE IN PATIENTS WITH MIDLINE GLIOMAS HARBORING HISTONE H3 K27M MUTATIONS. (11th November 2019) - Eduardo Silva Correia, Carlos; Pentsova, Elena; Lin, Andrew; Miller, Alexandra
Abstract: INTRODUCTION: The 2016 WHO classification describes a specific subtype of midline gliomas harboring histone 3 (H3) K27M mutations which compromise 15–40% of gliomas in children and young adults. Since we began to perform molecular profiling at Memorial Sloan Kettering Cancer Center (MSKCC) we have observed an increased prevalence of leptomeningeal disease (LMD) in this population. However, the true incidence and the clinical behavior of this group has not been well-defined. METHODS: This is a retrospective study of patients with H3K27M/I diffuse midline gliomas at MSKCC from 01/2012 to 01/2019. Mutations were identified through next-generation sequencing (NGS). RESULTS: We identified 24 patients. Median age was 21 (6–70) and 13 were male. Thirteen tumors were in the thalamus, 6 in the brainstem, 4 in the spinal cord, and 1 in the pineal region. H3K27M mutations were detected by NGS from tumor tissue in 21 patients, from cerebral spinal fluid (CSF) circulating tumor DNA (ctDNA) in 2 and from tissue and CSF ctDNA in one. LMD was diagnosed in 17/24 (71%) patients radiographically. Of these, 8 underwent LP: CSF cytology was positive in 2/8 and CSF ctDNA was detected in 3/3. All patients received RT and one or more lines of chemotherapy. At analysis, thirteen patients remain alive. Median time to last follow up for all patients was 14.2 months. Median time from diagnosis to LMD was 13.2 months (0–45.1), with median OS of 6.5 months (0.3–27) after diagnosis of LMD. CONCLUSION: Our study showed that more than two-thirds of the patients with H3 K27M diffuse midline developed LMD. Neuroaxis imaging should be performed in conjunction with CSF studies to diagnose LMD. Besides, CSF ctDNA represents an important tool to identify molecular profile of tumors when biopsy is not feasible or limited for the analysis.